Advocating for the rights of women migrant workers The Philippine government's revalida in the 64th session of the UN Committee on the Elimination of Discrimination Against Women (CEDAW).
This publication is a compedium of reports, arguments, and counter arguments that were presented during the UN CEDAW review process in 2015 & 2016, drawing special attention to the rights of women migrant workers.